Traditional Values Versus Inclusivity: A Semiotic Analysis of LGBT Narratives in Islamic Media Portals in Indonesia, Malaysia and America - Khadijah, Nur Sitti; Sujoko, Anang; Oktaviani, Fitri Hariana (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2024)
Media serves as a powerful tool in shaping public opinion and perspectives, particularly through Islamic organization-based media portals that play a crucial role in influencing perceptions of the LGBT community. This study examines the construction of LGBT narratives in the media portals NU Online, Ummah Today, and CAIR, utilizing the social semiotic method developed by M.A.K. Halliday and drawing on the theories of Nick Couldry and Andreas Hepp to explain the role of media construction. A total of 48 units of analysis were conducted, comprising 29 publications from NU Online in 2016, 9 publications from Ummah Today in 2022, and 10 publications from CAIR in 2016. The findings indicate that Ummah Today and NU Online tend to reinforce traditional values by rejecting issues such as LGBT, whereas CAIR adopts a more inclusive approach, especially in times of crisis, aiming to dispel Islamophobia and promote human rights for minority groups. This research reveals how media practices shape identities and social meanings across various cultural contexts and highlights significant social, cultural, and political implications of language in maintaining or challenging existing power structures and social norms.